Inhibition of Sodium Hypochlorite Antimicrobial Activity in the Presence of Bovine Serum Albumin - Pappen, Fernanda Geraldes; Qian, Wei; Aleksejuniene, Jolanta; Leonardo, Renato de Toledo [UNESP]; Leonardo, Mario Roberto; Haapasalo, Markus (Elsevier B.V., 2010)
Introduction: This study investigated the inhibition of the antimicrobial activity of sodium hypochlorite (NaOCl) by bovine serum albumin (BSA). The killing of Enterococcus faecalis, Candida albicans, Staphylococcus epidermidis, and Escherichia coil by NaOCl in concentrations from 2% to 0.03% was measured in the presence of BSA in concentrations between 6.7% and 0.1%. Methods: NaOCl, BSA, and microorganism suspensions were mixed, and, after 30 seconds, 6 minutes, and 30 minutes, samples were taken and NaOCl was inactivated by 5% sodium thiosulphate. The microbes were incubated in tryptic soy broth broth for up to 7 days for the detection of growth. Results: All microorganisms were killed within 30 seconds by 0.03% NaOCl when BSA was not present. High concentrations of BSA significantly reduced the antimicrobial activity of NaOCl against the four species. Conclusions: The inhibition of sodium hypochlorite by BSA was directly dependent on their quantitative relationships. The result partly explains the poorer performance in vivo of NaOCl as compared to in vitro experiments. (J Endod 2010;36:268-271)
Keywords: Antimicrobial effect; bovine serum albumin; sodium hypochlorite